First‐line sorafenib sequential therapy and liver disease etiology for unresectable hepatocellular carcinoma using inverse probability weighting: A multicenter retrospective study. (24th October 2021) - Shimose, Shigeo; Hiraoka, Atsushi; Nakano, Masahito; Iwamoto, Hideki; Tanaka, Masatoshi; Tanaka, Takaaki; Noguchi, Kazunori; Aino, Hajime; Ogata, Kei; Kajiwara, Masahiko; Itano, Satoshi; Yokokura, Yoshinori; et al.
Abstract: Background and Aims: Sequential therapy with molecular‐targeted agents (MTAs) is considered effective for unresectable hepatocellular carcinoma (HCC) patients. This study purposed to evaluate the efficacy of sequential therapy with sorafenib (SORA) as a first‐line therapy and to investigate the therapeutic impact of SORA in nonalcoholic fatty liver disease (NAFLD) or nonalcoholic steato hepatitis (NASH)‐related HCC. Methods: We evaluated 504 HCC patients treated with SORA (Study‐1). The times of administration for sorafenib from 2009 to 2015, 2016 to 2017, and 2018 and later were defined as the early‐, mid‐, and late‐term periods, respectively. Among them, 180 HCC patients treated with SORA in addition to MTAs in the mid‐ and late‐term periods were divided into groups based on disease etiology (NAFLD or NASH [ n  = 37] and viral or alcohol [ n  = 143]), and outcomes were compared after inverse probability weighting (IPW) (Study‐2). Results: Overall survival (OS) of HCC patients who received sequential MTA therapy after first‐line SORA was significantly longer. The median survival times (MST) were 12.6 versus 17.6 versus 17.4 months in the early‐term group, mid‐term group, and the later‐time group (early vs. mid, p  = 0.014, early vs. later. p  = 0.045), respectively. (Study‐1). In Study‐2, there was no significant differences in OS between the Virus/alcohol group and the NAFLD/NASH group in patients who received sequential therapy (MST was 23.4 and 27.0 months p  = 0.173, respectively). The NAFLD or NASH, female sex, albumin‐bilirubin (ALBI) grade 2b, and major Vp (Vp3/Vp4) were significant factors for OS treated with SORA. Conclusions: Sequential therapy with SORA as the first‐line treatment improved the prognosis of unresectable HCC patients and was effective regardless of HCC etiology. Abstract : Sequential therapy with SORA as the first‐line treatment prolonged the prognosis of unresectable HCC patients and was effective regardless of HCC etiology.